2020
DOI: 10.1177/0306624x19900979
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Domestic Abuse Program for Australian Indigenous Offenders

Abstract: The subject of this study is to assess the effectiveness of a culture-neutral domestic abuse program (DAP) developed for offenders with domestic and family violence histories, when used for Australian Indigenous offenders, serving community-based supervised orders. The study employed a retrospective quasi-experimental research design and intention-to-treat program definition for 953 DAP-treated men and propensity score–matched controls, from diverse cultural, religious, and racial backgrounds, 19% being Indige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…Regarding sociodemographic variables, literature revealed that younger, unemployed, and single perpetrators, belonging to a racial/ethnic minority, less educated, and with a lower income tend to be more likely to dropout from intervention (e.g., Askeland & Heir, 2013;Blatch et al, 2020;Cantos et al, 2015;LaPosta et al, 2019;Timko et al, 2015). On the opposite, older, employed, married, Caucasian, with higher income, and more educated perpetrators (e.g., Askeland & Heir, 2013;Bowen & Gilchrist, 2006;Catlett et al, 2010;Gover et al, 2011) demonstrate lower dropout rates.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding sociodemographic variables, literature revealed that younger, unemployed, and single perpetrators, belonging to a racial/ethnic minority, less educated, and with a lower income tend to be more likely to dropout from intervention (e.g., Askeland & Heir, 2013;Blatch et al, 2020;Cantos et al, 2015;LaPosta et al, 2019;Timko et al, 2015). On the opposite, older, employed, married, Caucasian, with higher income, and more educated perpetrators (e.g., Askeland & Heir, 2013;Bowen & Gilchrist, 2006;Catlett et al, 2010;Gover et al, 2011) demonstrate lower dropout rates.…”
Section: Introductionmentioning
confidence: 99%
“…However, significant concerns have been expressed about adopting a narrow knowledge‐driven approach to evidenced‐based justice policy from those in colonised countries such as Australia, Aotearoa New Zealand, and Canada (Blagg & Anthony, 2019; Dudgeon & Milroy, 2014). For example, it has been argued that offender rehabilitation policy and programmes are rooted within a ‘medical model’ (Freiberg & Carson, 2010, p. 155) of criminal behaviour, and rely on deficit‐based, universal, and reductionist approaches which separate offending behaviour from both context and environment (see also Blatch et al, 2020; Weatherburn, 2014). This has led, it is argued, to a research policy and programme environment that is grounded in ethnocentric and colonial practices, supported by knowledge production that is owned and legitimised through Western institutions (Tauri, 2017; Teo, 2015).…”
Section: Introductionmentioning
confidence: 99%